It takes two: Women’s empowerment in agricultural value chains in Malawi - Ragasa, Catherine; Malapit, Hazel J.; Rubin, Deborah; Myers, Emily; Pereira, Audrey; Martinez, Elena M.; Heckert, Jessica; Seymour, Greg; Mzungu, Diston; Kalagho, Kenan; Kazembe, Cynthia; Thunde, Jack; et al. (International Food Policy Research Institute, 2021)
Inclusive agricultural value chains (VCs) are potential drivers for poverty reduction, food security, and women’s empowerment. This report assesses the implementation of the Agricultural Technical and Vocational Education Training for Women Program (ATVET4Women) that aims to support women with vocational training and market linkages in priority agricultural value chains. This report focuses on Malawi, one of the six pilot countries of the ATVET4Women; and focuses on vegetable value chains in which some non-formal training sessions have been conducted as of October 2019. This report presents (1) program experience of stakeholders; (2) evidence of program benefits and challenges among ATVET4Women non-formal training graduates; and (3) baseline data on value chain and empowerment indicators, using a pilot household survey-based instrument for measuring women’s empowerment in agricultural value chains (pro-WEAI for market inclusion) and supplementary qualitative research. Results show graduates’ satisfaction and appreciation of the training provided, and some graduates reported having access to more lucrative markets as a result of the training. However, positive changes in several outcome indicators were reported by only some graduates: 30 percent of graduates reported increased production and sales. There is no significant difference in the reported changes and levels of vegetable production and income between graduates and non-graduates. Qualitative findings suggest that constraints to accessing agricultural inputs and funds to upgrade their production may be why there are no measured differences. Results on empowerment status reveal that 73 percent of women and 85 percent of men in the sample are empowered, and 73 percent of the sample households achieved gender parity. The main contributor of disempowerment among women and men is lack of work balance and autonomy in income. Fewer women achieved adequacy in work balance than men. Adequacies in attitudes about domestic violence, respect among household members, input in productive decisions, and asset ownership are generally high for both women and men, but significantly lower for women. While this report is mainly descriptive and further analysis is ongoing, it offers some lessons and practical implications for improving ATVET4Women program implementation and its outcomes on women’s market access, incomes, and empowerment.